Relacions hipertextuals en Judit (1929), de Josep Maria de Sagarra - Rosselló, Ramon X. (Studia Romanica Posnaniensia, 2021)
This article is a monograph focusing on an analysis of the play Judit by Josep M. de Sagarra. The author’s only tragedy, and unique among his works, was first performed in Barcelona in 1929. It is a little-studied work, doubtless due to its lack of success with theatre audiences, although Sagarra himself had a high opinion of it. To carry out our analysis, we will make use of the analytic tools introduced by Gérard Genette in his Palimpsestes (1982) around hypertextuality and, more specifically, we will consider this work as a transformation of the biblical story, paying special attention to the new material Segarra brought to this text.